The incidence and prevalence of comorbid gastrointestinal, musculoskeletal, ocular, pulmonary, and renal disorders in multiple sclerosis: A systematic review - Marrie, Ruth Ann (Mult Scler, 2015)
BACKGROUND: As new disease-modifying therapies emerge a better knowledge of the risk of comorbid disease in multiple sclerosis (MS) is needed. OBJECTIVE: To estimate the incidence and prevalence of comorbid gastrointestinal, musculoskeletal, ocular, pulmonary, and renal disorders in MS. METHODS: We systematically reviewed the world literature by searching PUBMED, EMBASE, SCOPUS, the Web of Knowledge, and reference lists of retrieved articles. For selected articles, one reviewer abstracted data using a standardized form. The abstraction was verified by a second reviewer. The quality of all selected studies was assessed. For population-based studies we quantitatively assessed studies using the I(2) statistic, and conducted random effects meta-analyses. RESULTS: Study designs were heterogeneous with respect to populations, case definitions, and methods of ascertainment. Incidence of the studied comorbidities was rarely reported. Irritable bowel syndrome and chronic lung disease had a prevalence of more than 10% in the MS population. Irritable bowel syndrome, fibromyalgia, cataracts and glaucoma were more common than expected in the MS population. CONCLUSION: Although they have been the subject of less study than other comorbidities, irritable bowel syndrome, arthritis, and chronic lung disease are common in the MS population and occur more often than expected when compared to the general population.